Everyone in the group chat dies : a novel - Chilton, L. M. (Scout Press, 2025)
Kirby Cornell needs a break from everything: her crumbling apartment, her dead-end job, her sleazy landlord, her messy roommates, and, most of all, the terrible thing they all did. Luckily, that hasn't caught up with her just yet. Until a new message on their old group chat pops up: "Everyone in the group chat dies". It's the first text her ex-roommate Esme has sent for ages, but that's not the really weird thing. The really weird thing is that Esme died twelve months ago...